Lipophilic N‐Hydroxyphthalimide Catalysts for the Aerobic Oxidation of Cumene: Towards Solvent‐Free Conditions and Back. Issue 44 (13th July 2017) - Petroselli, Manuel; Melone, Lucio; Cametti, Massimo; Punta, Carlo
Abstract: A new class of lipophilic N ‐hydroxyphthalimide (NHPI) catalysts designed for the aerobic oxidation of cumene in solvent‐free conditions was synthesized and tested. The specific strategy proposed for the introduction of lipophilic tails on the NHPI moiety leads to lipophilic catalysts that—while completely preserving the activity of the precursor—allow the catalytic oxidation to be conducted in neat cumene, for the first time. The corresponding cumyl hydroperoxide is obtained in good yields (28–52 %) and with high selectivity (95–97 %), under mild conditions. Importantly, the presence of a polar solvent is no longer required to guarantee complete solubilization of the catalyst. On the other hand, the oxidation conducted in neat cumene reveals the unexpected necessity of using small amounts of acetonitrile to fully promote the hydrogen atom transfer process and prevent the catalyst from detrimental hydrogen‐bond (HB) driven aggregation. Abstract : The degrees of freedom : Novel lipophilic N ‐hydroxyphthalimide catalysts allowed the catalytic oxidation of neat cumene to be conducted for the first time, and revealed the limits of solvent‐free conditions, wherein hydrogen‐bond (HB) driven aggregation of the catalyst occurs.